İstinaf İncelemesinin Kapsamı - Karaca, Hilal Ölmez (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
Bu tezde istinaf kanun yolunda, bölge adliye mahkemeleri tarafından yapılacak incelemenin kapsamı HMK m.355 düzenlemesi çerçevesinde ele alınmıştır. Çalışmamızın ana konusunu, kanun koyucu tarafından benimsenen dar anlamda istinaf sisteminin yansıması olan istinaf sebepleri ile sınırlı olarak inceleme yapılması ve bu kuralın istisnasını oluşturan kamu düzenine aykırılık incelemesi oluşturmaktadır. Bölge adliye mahkemesi, ilk derece mahkemesinin hatalı kararını, taraflarca ileri sürülen istinaf sebepleri çerçevesinde inceleyecek ve karar vereccektir. Bu kuralın istinasnası yine kanun koyucu tarafından belirlenen kamu düzenine aykırılık bulunması halidir. İlk derece mahkemesi kararında kamu düzenine aykırılık bulunması halinde bölge adliye mahkemesi, re’sen bu aykırılığı dikkate alarak karar verecektir.

In this thesis, the scope of the review to be carried out by the regional courts of appeal in the appeal process is handled within the frame of article 355 of the Code of Civil Procedure. The main subject of our study is the examination limited to the grounds of appeal, which is the reflection of the narrow sense appeal system adopted by the legislator, and the examination of the violation of public order, which constitutes the exception to this rule. The regional courts of appeal shall examine and decide on the erroneous or incomplete decision of the court of the first instance within the framework of the grounds of appeal alleged by the parties. The exception to this rule is in cases where there is a violation of the public order determined by the legislator. If there is a violation of public order in the decision of the court of the first instance, the regional court of appeal will decide ex officio by taking this contradiction into account.
Scope of Appeal Review
Keywords: İstinaf Kanun Yolu; Dar Anlamda İstinaf Sistemi; İstinaf İncelemesinin Kapsamı; İstinaf Sebepleri; İstinaf Sebepleri İle Sınırlı İnceleme Yapılması; Kamu Düzenine Aykırılık; Law of Appeal; Appeal System in The Narrow Sense; Review of Appeal; Scope of The Review of Appeal; Grounds for Appeal; Limited Review with The Grounds of Appeal; Violation of Public Order